Application of the SDS-PAGE method for the characterisation of winter wheat flour quality - Tóth, Árpád; Sipos, Péter; Borbély, Mária; Uri, Csilla; Győri, Zoltán (Acta Agraria Debreceniensis, 2006)
The principle, development and importance of the SDS-PAGE method are presented in this article. The SDS-PAGE method has become one of the basic methods of molecular biological research, because it is widely applicable and its sensitivity is excellent in the separation of wheat storage proteins.We have shown the application of this method with a concrete example. It was also tested whether, it was possible to obtain a better baking quality product from a large amount of poor quality less valuable wheat by fractioning the flour according to particle sizes after grinding. We studied the rheological properties of flours with different particle size fractions from the original flour. The baking quality of the original flour was B2. The 125-90 and 90-63 μm fractions have significantly better baking quality (B1) than the original flour. The protein contents of these flour fractions were also significantly higher than the protein content of the original flour. We had a question: what has influenced the baking quality: the protein content or other factors? We searched for an explanation on these results in the protein composition of the flour samples. We studied the distribution of glutenin-fractions by SDS-PAGE method and evaluated them. We found with correlation analysis that the amount of LMW-Glutenin D-group (52-60 kDa) is in a strong, negative correlation to the baking quality (r = – 0.855*). Therefore, the baking quality of flour samples was influenced by this glutenin fraction.